KESERAGAMAN TETESAN PADA IRIGASI TETES SISTEM GRAVITASI: Emission Uniformity on Gravitational Drip Irrigation System - Saidah, Humairo; Yasa, I Wayan; Hardiyanti, Ernita (Jurusan Teknik Sipil Fakultas Teknik Universitas Mataram, 2014)
Since water availability in arid area is very limited, the technology of water-saving irrigation system is extremely needed. Gravitational drip irrigation system is one of modification drip irrigation system that very feasible to apply, due to using familiar materials that will be mostly easy to find and no high skill and sophisticated technology knowledge is needed. This research conducted an experimental model of drip irrigational system with a reservoir placed on the height of 3 meters. Then observations were made by measuring of water that collected in a glass collector on each emitter placed along lateral pipe 6 meters long. The pipe fitted on a slope of 0%, 0.3%, 0.4% and 0.5%, then be compared its emission uniformity. The results showed that the best emission uniformity coefficient obtained at 0.3% pipe slope compared with the others with emission uniformity coefficient more than 85% and in a category of very good emission uniformity. Then emission uniformity coefficient also increases while increasing the duration of flows. So the longer time of flows shows the better emitters performance.